Munda Makeover - Using digital channels to deliver bundled agriculture, climate, and financial information services in Zambia: IPSR Innovation Package and Scaling Readiness Report - Chilambe, Pedro Anglaze; Patricia, Gichinga; Girvetz, Evan Hartunian; Kang'ethe, Edwin (CGIAR System Organization, 2023)
This is a report on an innovation packaging exercise for the Munda makeover innovation. Munda makeover innovation packaging is being implemented by the Alliance of Bioversity International and the International Center for Tropical Agriculture (ABC) and partners. It is part of the work under the Diversification in East and Southern Africa (Ukama Ustawi) Regional Integrated Initiative of the CGIAR.